2022
DOI: 10.3389/fpls.2022.960750
|View full text |Cite
|
Sign up to set email alerts
|

Rahnella aquatilis JZ-GX1 alleviates iron deficiency chlorosis in Cinnamomum camphora by secreting desferrioxamine and reshaping the soil fungal community

Abstract: Plant growth-promoting rhizobacteria are important for improving plant iron nutrition, but the interactions among inoculants, host plants and soil microorganisms have not been greatly explored. Rahnella aquatilis JZ-GX1 was applied to treat the increasingly serious iron deficiency chlorosis in Cinnamomum camphora, and the resulting improvement in chlorosis was determined by assessing the contents of chlorophyll, active iron, Fe2+ and antioxidant enzymes in leaves, the effects on the soil microbial community an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Notably, 3‐trans‐caffeoyltormentic acid showed a significant positive correlation with the dominant fungi of Saitozyma and Protoglossum (Figure 7), and this phenolic may be the preferred substrate for both of these fungi. It was reported that 3‐trans‐caffeoyltormentic acid is derived from trans‐cinnamic acid (Moeenfard et al, 2014), has insect resistance (Lv et al, 2022), and is associated with pathogenic fungal communities (Kong et al, 2022). Whether Saitozyma and Protoglossum are potentially harmful to soil and plant health needs to be further verified.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, 3‐trans‐caffeoyltormentic acid showed a significant positive correlation with the dominant fungi of Saitozyma and Protoglossum (Figure 7), and this phenolic may be the preferred substrate for both of these fungi. It was reported that 3‐trans‐caffeoyltormentic acid is derived from trans‐cinnamic acid (Moeenfard et al, 2014), has insect resistance (Lv et al, 2022), and is associated with pathogenic fungal communities (Kong et al, 2022). Whether Saitozyma and Protoglossum are potentially harmful to soil and plant health needs to be further verified.…”
Section: Discussionmentioning
confidence: 99%
“…R. aquatilis is considered to have great potential as an antagonist to many bacterial pathogens (Laux et al, 2002;El-Hendawy et al, 2003;Chen et al, 2007Chen et al, , 2009Li et al, 2020a). Also, plant growth promotion by R. aquatilis has been reported (Yuan et al, 2020;Li et al, 2021;Kong et al, 2022;Landa-Acuña et al, 2023). Rahnella aquatilis strains 17 and 55 has been previously reported as potential biological control agents of bacterial spots of tomato caused by Xanthomonas campestris pv.…”
Section: Introductionmentioning
confidence: 99%